2016
DOI: 10.1016/j.eats.2016.05.007
|View full text |Cite
|
Sign up to set email alerts
|

Arthroscopic 360° Capsular Release for Adhesive Capsulitis in the Lateral Decubitus Position

Abstract: Idiopathic adhesive capsulitis of the shoulder is a relatively common condition that results in pain and loss of motion due to capsular thickening and fibrosis. Most cases are successfully treated with conservative management including physical therapy and intra-articular steroid injections. If conservative management fails, arthroscopic capsular release allows precise release of thickened capsular tissue with a lower risk of complications and less soft-tissue trauma than manipulation under anesthesia alone. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
25
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(25 citation statements)
references
References 17 publications
0
25
0
Order By: Relevance
“…Additionally, increased visualization of the inferior capsule when performing arthroscopic shoulder stabilization in the LD position may be advantageous in patients with 360° labral tears. 12,37 Furthermore, surgeon familiarity with the procedure and skilled technique likely contribute significantly to positive outcomes. 15…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, increased visualization of the inferior capsule when performing arthroscopic shoulder stabilization in the LD position may be advantageous in patients with 360° labral tears. 12,37 Furthermore, surgeon familiarity with the procedure and skilled technique likely contribute significantly to positive outcomes. 15…”
Section: Discussionmentioning
confidence: 99%
“…3 Arthroscopic capsular release has been described previously for patients with frozen shoulder who are recalcitrant to non-surgical management. [4][5][6][7][8][9][10][11][12][13] Compared to manipulation under anaesthesia which carries a risk of iatrogenic fracture, arthroscopic capsular release allows for a controlled release of a tight glenohumeral joint capsule and can be combined with a selective manipulation. 14 Ogilvie-Harris and Myerthall in 1997 reported good outcomes in their series of 17 patients who underwent arthroscopic capsular release for the diabetic frozen shoulder.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, capsular release involves the precise release of thickened capsular tissue, allowing for rapid short-term improvements in range of motion and pain reduction. 7 , 8 Bhargav and Murrell 4 reported that after capsular release, the severity of pain at rest decreases from moderate to mild and that range of motion in forward flexion increases from 70° to 100° by 1 week after surgery. Moreover, patients undergoing capsular release are encouraged to start using their shoulder as soon as possible after surgery, 22 perhaps aiding in return to sport and the confidence to do so to a higher level within the 6-month follow-up period.…”
Section: Discussionmentioning
confidence: 99%